ISOPM: framework for IT/IS outsourcing project management - Fraga, Maria da Glória (2017)
Information Systems (IS) and Information Technologies (IT) are fundamental elements for the competitiveness of organizations. Thus, an efficient development of IT/IS projects is a key factor for business success. Nowadays companies are increasingly outsourcing their activities, including the development of IT/IS projects. However, the results of investments often lead to frustration and are far from meeting the expectations. Bearing this in mind, this paper proposes a new framework ISOPM - that identifies the most relevant activities for the IT/IS outsourcing projects management, aiming to contribute to the study and development of this specific area of project management.